3D Echocardiographic Assessment of Right Ventricular Involvement of Left Ventricular Hypertrabecularization from a New Perspective - Márton Horváth; Kristóf Farkas-Sütő; Flóra Klára Gyulánczi; Alexandra Fábián; Bálint Lakatos; Anna Réka Kiss; Kinga Grebur; Zsófia Gregor; Balázs Mester; Attila Kovács; Béla Merkely; Andrea Szűcs (Journal of Imaging, 2025)
Right ventricular (RV) involvement in left ventricular hypertrabeculation (LVNC) remains under investigation. Due to its complex anatomy, assessing RV function is challenging, but 3D transthoracic echocardiography (3D_TTE) offers valuable insights. We aimed to evaluate volumetric, functional, and strain parameters of both ventricles in LVNC patients with preserved left ventricular ejection fraction (EF) and compare findings to a control group. This study included 37 LVNC patients and 37 age- and sex-matched controls. 3D_TTE recordings were analyzed using TomTec Image Arena (v. 4.7) and reVISION software to assess volumes, EF, and global/segmental strains. RV EF was further divided into longitudinal (LEF), radial (REF), and antero-posterior (AEF) components. LV volumes were significantly higher in the LVNC group, while RV volumes were comparable. EF and strain values were lower in both ventricles in LVNC patients. RV movement analysis showed significantly reduced LEF and REF, whereas AEF remained normal. These findings suggest subclinical RV dysfunction in LVNC, emphasizing the need for follow-up, even with preserved EF.